Admissibility of Statements Obtained as a Result of “Private Torture” or “Private” Inhuman Treatment as Evidence in Criminal Proceedings: Emergence of a New European Standard? - Małgorzata Wąsek-Wiaderek (Revista Brasileira de Direito Processual Penal)
This article presents a critical approach to the position of the European Court of Human Rights on the admissibility of evidence (recorded statements) obtained as a result of “private torture or inhuman treatment”, while such recordings were produced outside of and for purposes other than the criminal proceedings. In accordance with the recent judgment of the Court (case Ćwik v. Poland), the use of this evidence in the criminal proceedings conducted against a third party, not against a tortured person, renders such proceedings as a whole automatically unfair, in breach of Article 6 of the European Convention on Human Rights. In the author’s opinion, the ECtHR does not attach adequate importance to the fact that the use of such evidence cannot have any impact on the scope or level of protection against torture or other forms of cruel treatment, provided in the framework of criminal proceedings. It is argued in this paper that recorded statements produced prior to criminal proceedings and not for purposes of those proceedings by private individuals, without the instigation, consent, or acquiescence of public officials, by methods contrary to Article 3 of the Convention, shall be admissible evidence. Consequently, the European Court should not have questioned the admissibility of such evidence, but rather assess the fairness of criminal proceedings as a whole.